Breeding biology of amphibians in temporary water bodies (Zoological Records and Reviews, 2023)
Temporary water bodies -- seasonal ponds, vernal pools, rain-fed ditches, and ephemeral wetlands that lack permanentwater connection -- represent critical breeding habitats for a disproportionate number of European amphibian species,whose reproductive biology has evolved around the predictable seasonal hydroperiod of these systems and the relativeabsence of fish predators that characterises most temporary aquatic habitats. This review synthesises evidence from 176primary studies (2003-2023) examining the breeding biology, reproductive success, and conservation status of Europeanamphibians in temporary water body habitats across Mediterranean, Atlantic, Continental, and Boreal biogeographicalregions. We document breeding phenology, reproductive strategies, larval development timing, hydroperiodrequirements, and community assembly patterns for 24 European amphibian species with temporary water bodyassociations. Breeding season onset has advanced by a mean 6.4 +- 1.8 days per decade across 18 monitored species(1990-2022), with Mediterranean species showing the greatest advancement (8.4 days/decade) driven by earlier andmore variable winter rainfall patterns. Temporary pond loss across Europe exceeds 73% since 1900, with hydroperiodshortening due to climate change and groundwater abstraction documented at 68.4% of monitored temporary ponds.Minimum hydroperiod requirements for successful metamorphosis are species-specific (range 42-128 days) andrepresent the critical vulnerability for species in drying landscapes. Conservation interventions -- pond creation,hydroperiod extension through impermeable liners, grazing management to maintain open structures -- are evaluatedagainst species-specific breeding biology requirements. Implications for EU Habitats Directive Article 17 assessment andNature Restoration Law freshwater habitat restoration targets are discussed.